2005
DOI: 10.1093/jurban/jti065
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity Differences in the Validity of Self-Reported Drug Use: Results from a Household Survey

Abstract: Data were analyzed from a multistage probability household survey of over 600 adults, ages 18-40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 23 publications
(24 reference statements)
4
45
2
Order By: Relevance
“…Table 3 shows the result from the final adjusted negative binomial regression model. In contrast to population and community-based studies, (Fendrich & Johnson 2005;Johnston & O'Malley 1997;Shillington & Clapp 2000) blacks on average reported inconsistently on less than half the number of substances than whites (incidence rate ratio = 0.41, 95% confidence interval = (0.31, 0.53)). Clients of Hispanic origin in the ATM sample provided inconsistent responses on only slightly fewer substances on average than did whites (incidence rate ratio = 0.91, 95% confidence interval = (0.85, 0.98)).…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Table 3 shows the result from the final adjusted negative binomial regression model. In contrast to population and community-based studies, (Fendrich & Johnson 2005;Johnston & O'Malley 1997;Shillington & Clapp 2000) blacks on average reported inconsistently on less than half the number of substances than whites (incidence rate ratio = 0.41, 95% confidence interval = (0.31, 0.53)). Clients of Hispanic origin in the ATM sample provided inconsistent responses on only slightly fewer substances on average than did whites (incidence rate ratio = 0.91, 95% confidence interval = (0.85, 0.98)).…”
Section: Resultscontrasting
confidence: 67%
“…By contrast, the accuracy of selfreported substance use and its effect on prevalence and age at first use estimates has been widely studied by epidemiologists and prevention researchers using both community and school-based samples (Appel et al 2001;Colon et al 2001;2002;Fendrich 2005;Fendrich et al 1999;Fendrich & Rosenbaum 2003;Fendrich & Vaughn 1994;Johnson & Mott 2001;Johnston & O'Malley 1997;Morral et al 2000;Percy et al 2005;Shillington & Clapp 2000;Tassiopoulos et al 2006). In general, the literature on the reliability and validity of substance use reports is derived from research studies with uncertain relevance to treatment populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, study participants may misrepresent drug use due to social desirability bias, stigma, poor recall, poorly worded questions, or poorly worded response categories in surveys and interviews [23,24], all of which could result in misclassification of measured exposures. Although studies have shown that the use of Audio Computer-Assisted Self Interview (ACASI) increases reporting of sensitive and stigmatized behaviors [25,26], research suggests that the validity of self-reported drug use varies by population [27], race/ ethnicity [28][29][30], mental health [27], and drug treatment status [22,31,32], although not by gender [30,33]. Accuracy has varied in studies of arrestee populations [34,35] but have been reported as higher in groups sampled in emergency department and STI clinics [34].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses from a previous paper utilizing the same data suggests that compared with the rest of the sample, African Americans, females, and those of lower socioeconomic status (SES) were overrepresented in the subgroup employed in this study. 28 …”
Section: Drug Testingmentioning
confidence: 99%
“…A comparison of concordance by race/ethnicity presented in an earlier paper using these data showed that rates varied from 90% to 99% for crack/cocaine and 87% to 100% for marijuana. 28 Drug Use Classification For the purposes of this paper, we employed the use of two indicators of substance use: self-reports of alcohol, marijuana, and crack/cocaine use and saliva or urine tests for marijuana and crack/cocaine use. Respondents testing positive for marijuana or crack/cocaine on either the saliva or urine tests were considered as positive cases for use of that substance, respectively, whereas respondents testing negative for use of a particular substance on both tests were considered as negative cases for use of that substance.…”
Section: Drug Test Concordancementioning
confidence: 99%